Analisis Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan CV. Naya Muda Konstruksi Pekanbaru - Arvin Arief Ismael; Hari Wibowo Utomo (CV. Syntax Corporation Indonesia, 2021)
This study aims to describe the problems that exist on the CV. Naya Muda Konstruksi, where the development ofa service business in the field of construction and construction servicesimprovement, becomes an opportunity for small companies for sub-sectoral jobs. Take advantage of opportunities to reach consumers, creating competition between similar development and improvement service companies. This also makes every company must innovate a creative marketing strategy in selling services offered to target targets. CV. Naya Muda Konstruksi is one of the service companies, which was established in 2010 and is engaged in construction services and construction services improvement. Kendala that often occurs is when the schedule of work on the completed project is not on time. In these circumstances,the need forleadership direction, company motivation and good work discipline between fields of work in CV. Naya Muda Konstruksi so that it can follow up employee performance as soon as possible so as not to cause disappointment from consumers. Based on the description above, the author is interested in conducting research that will be poured in the form of scientific writing entitled